PENGEMBANGAN MODEL PRAKTIKUM SAINS UNTUK SISWA TUNANETRA MELALUI PENDEKATAN KONSTRUKTIVIS SERTA APLIKASINYA PADA PENDIDIKAN INKLUSIF - Juli Astono (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Developing a Model of a Science Practicum for Blind Students Through the Constructivist Approach and Its Application in the Inclusive Education. This study aims to develop a model of a science practicum for blind students through the constructivist approach for both schools running inclusive education and those for the handicapped. The research stages included: (1) developing practicum devices for realistic science, i.e. voice equipment, (2) developing a practicum model using the constructivist approach, and (3) developing an evaluation model for the sclence learning process and product. The study employed a spiral model by Cennamo and Kalk (2005:6), consisting of (1) definition, (2) design, (3) demonstration, (4) development, and (5) presentation. The products include: (1) voice equipment to measure temperature and electricity voltage that the students use in the science practicum, (2) a realistic practicum model that motivates and trains the students to be active and autonomous as suggested by the constructivist approach, and (3) the improvement of the students discussion activities based on the eveluation model. Keywords: science practicum model, inclusive education, blind students